Variations in online self-regulated learning abilities among Chinese K-12 teachers across different regions and levels - Zhao, Yan; Li, Yu; Sun, Zhong Hua; Jiang, Qiang; Zhao, Shuang (Frontiers in Psychology, 2024)
Introduction: Online self-regulated learning (OSRL) is crucial for online learners' success and lifelong learning. This study investigated the OSRL characteristics of K-12 teachers in China, who embody the dual roles of learners and educators. It also analyzed the differences in OSRL abilities across different genders, education stages, and school locations, and examined the correlation between education qualifications, years of service, and OSRL abilities.Methods: A self-report measure was used to assess K-12 teachers' OSRL, with data collected from 1,443 K-12 teachers (394 males and 1,049 females) in northeastern China. Descriptive statistical analysis was utilized to explore the characteristics of their OSRL. Independent t-tests and ANOVA were employed to investigate differences in OSRL among different genders, regions, and educational stages. Correlation analysis was conducted to examine the relationships between education qualifications, years of service, and OSRL among K-12 teachers.The data analysis revealed that K-12 teachers scored the lowest in Online Learning Self-Efficacy (OLSE), followed by Online Learning Management Strategies (OLMS), and then Online Learning Resource Management (OLRM). Notably, urban K-12 teachers exhibited higher OLSE abilities than their rural counterparts, while high school teachers scored higher in OLSE and OLMS compared to primary school teachers. Furthermore, a positive correlation was observed between education qualifications and K-12 teachers' OLSE, whereas a negative correlation was identified between years of service and K-12 teachers' OLSE.The findings reveal an uneven development across various dimensions of online selfregulated learning among K-12 teachers, necessitating support for the advancement of OLSE, OLMS, and OLRM. Particular attention should be given to the OLSE of teachers with longer teaching years and rural teachers. Encouraging K-12 teachers with lower education qualifications to pursue further education is also recommended. This study provides evidence and a novel perspective for teacher educators to develop online professional development programs, which is significant for optimizing online learning experiences and enhancing educational outcomes.